Science and Technology Facilities - Moonen, Jean-Marie (OECD Publishing, 2004)
These four articles relate to science and technology infrastructure for secondary and tertiary institutions. The first article presents a view on approaches to teaching science in school and illustrates ideal science facilities for secondary education. The second piece reports on work underway to improve the Science Complex at the Université du Québec à Montreal. The third describes a secondary level vocational training centre devoted to new technologies in Quebec. The fourth article visits an Australian science and mathematics specialist school
Keywords: Education